2011
DOI: 10.1017/s0007114511006027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary strawberry powder on blood lipids and inflammatory markers in obese human subjects

Abstract: Obesity is a strong risk factor for the development of CVD, hypertension and type 2 diabetes. The overall goal of the present pilot study was to feed strawberries, in the form of freeze-dried powder, to obese subjects to determine whether dietary strawberries beneficially altered lipid profiles and reduced blood markers of inflammation compared with a control intervention. A total of twenty healthy subjects (thirteen females and seven males) aged between 20 and 50 years with a BMI between 30 and 40 kg/m 2 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 45 publications
6
81
1
2
Order By: Relevance
“…In order to provide a concentrated source of polyphones, fiber and micronutrients (table 2) for subjects with T2D, 50 g of FDS, equivalent to 500 g of fresh strawberries or 2 servings of fresh strawberries, was selected as a daily supplement for a period of 6 weeks. The supplement dose was obtained according to previous studies that demonstrated cardiovascular health benefits and compliance with dosing of 50 g of FDS [19,20,21,22,23]. The prescribed dose was also based on the benefits of adding at least two servings of fruits with low glycemic index to the dietary plan of patients with diabetes [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to provide a concentrated source of polyphones, fiber and micronutrients (table 2) for subjects with T2D, 50 g of FDS, equivalent to 500 g of fresh strawberries or 2 servings of fresh strawberries, was selected as a daily supplement for a period of 6 weeks. The supplement dose was obtained according to previous studies that demonstrated cardiovascular health benefits and compliance with dosing of 50 g of FDS [19,20,21,22,23]. The prescribed dose was also based on the benefits of adding at least two servings of fruits with low glycemic index to the dietary plan of patients with diabetes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Results from Wilson et al [30] and DeFuria et al [31] postprandial researches might provide more evidence for the latter metabolic mechanisms. Though results from studies which had investigated the effects of FDS on metabolic features of obese, hyperlipidemic subjects or subjects with metabolic syndrome revealed no significant changes in serum glucose concentration [19,20,21,22,23]. In previous studies the effect of FDS on glycated Hb was not investigated due to the shorter intervention period, lesser sample size and subjects having metabolic complications other than diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Longerterm strawberry supplementation has been shown to improve multiple CVD risk factors (16)(17)(18)(19)(20)(21)(22)(23)(24)(25), but less is known about the acute effects of strawberries in the context of a fat-containing meal. A modest attenuation of the 6-h postprandial triglyceride, insulin, and oxidized LDL response was found in overweight hyperlipidemic adults when 10 g freeze-dried strawberry powder was incorporated into a meal with 30 g total fat (26,27).…”
Section: Introductionmentioning
confidence: 99%